Resistências de povos e comunidades tradicionais ante o Estado e a colonialidade (SER Social, 2023)
In this article, we discuss how colonialism operated and continues to operate forms of violence against traditional peoples and communities. These collectives resist the overcoding processes of their territories by the State and by capital holders; and fight for access to rights and recognition of their modes of existence. In recent years, legislation and conventions, national andinternational, have been drawn up that deal with issues related to these peoples, however, they are not guaranteed that their lands will be demarcated. On the contrary, state policies to expand extractivism and monocultures have advanced, dismantling their living territories. The ethnographic research on which this article is based was carried out with the Rede Puxirão de Povos e Comunidades Tradicionais do Paraná – an organization that brings together indigenous people, quilombolas, faxinalenses, cipozeiros, slanders, artisanal fishermen and healers –, seeking to understand their forms of resistance to coloniality.